The Main Directions of Modernization of Professional Education In Uzbekistan - Murodulla Makhmudovich Kholmukhamedov (Research Parks Publishing LLC, 2022)
This article discusses the professional education system in Uzbekistan, the development of professional education standards and training programs based on the requirements of the international and local labor market and learning outcomes, and the modernization of the network of educational institutions.